Political participation of retired people towards a future for all ages – from Portugal to Europe - Teresa (Magyar Gerontológia, 2025)
In this presentation, I will present the project ‘Sowing a future for all ages’, developed between August and December 2024 by a Portuguese association made up exclusively of retired people. The project focused on demanding rights from political decision-makers, in an exercise of full citizenship and effective political participation.